Predicting Student Performance using Data Mining - Christina, Mabel (International Journal of Computer Sciences and Engineering, 2025)
Data mining focuses on collection information from knowledge bases or data warehouses and therefore the info collected that had never been famous before, it's valid and operational. today instructional data processing is associate rising discipline, involved with varied Approaches like Predicting student performance, Analysis and visual image of information, Providing feedback for supporting instructors, Recommendations for college students, Social network analysis and then thereon mechanically extracts that means from giant repositories of information generated by or associated with people's learning activities in instructional setting. One of the most important challenges is to enhance the standard of the academic processes therefore on enhance student’s performance. Thus, it's crucial to line new ways and plans for an improved management of the present processes. This model helps to predict student’s future learning outcomes mistreatment knowledge sets of senior students